Vacation wars - Quinn, Meghan (Montlake, 2023)
Spending the weeks before her sister's wedding in Santorini, Tessa, trying to avoid her sister's matchmaking attempts, finds an ally in her childhood crush, Myles, who works at the resort, and together they navigate their way through their families' antics, discovering their past feelings may have a future.